Diseño de las áreas de almacenamiento en la bodega de Agofer - DufercoGroup. (2021)
The objective of this thesis is to carry out a design of the storage areas, which allows to improve the distribution of their spaces and the dispatch and storage processes, in the warehouse of the company Agofer DufercoGroup, Villavicencio branch. The work is composed of 3 chapters, which make up the body of the research, in which a descriptive and applied research with qualitative orientation was used, based on the exact description of the processes carried out by its workers and the description of their areas storage, first of all, a diagnosis of the current situation of the winery was made, all this through techniques and mechanisms of industrial engineering, such as the direct observation technique and tools such as the cause-effect diagram, checklist, the interview and the route diagram in order to establish the process for warehouse management in the company, through these tools a true diagnosis was obtained, determining that the company currently does not have an adequate distribution, therefore a proposal was established improvement in the processes and a design of the storage area by means of a software called Corelap, it was determined It concluded that the design proposed by the research is viable to improve the distribution of the departments with a greater close relationship and the processes carried out for the dispatch of the products, thus reducing the processes and times carried out in the winery. This project is based on maintaining a disciplined supervision over all operations carried out in the warehouse and an adequate distribution of the product, in order to strive to achieve the objectives set by the organization and thus provide an excellent delivery service to its customers.